Combining a one-dimensional empirical and network solver with computational fluid dynamics to investigate possible modifications to a commercial gas turbine combustor - Morris, Reuben Montresor (University of Pretoria, 2013)
Dissertation (MEng (Mechanical))--University of Pretoria, 2008.